Effectiveness of linguistic features for attracting audience: A study of coworking space websites’ headlines - Firdausi, Maulidina Marlita; Yannuar, Nurenzia; Basthomi, Yazid (Universitas Muhammadiyah Sidoarjo, 2022)
The emergence of coworking spaces have disrupted conventional working lifestyle and built a new trend: shared office space which highlights community-based services. Our paper looks at how this new business promotes their service through advertising language in online media. Advertising language in previous studies have mainly focused on slogans found in printed advertisements (Pratiwi et al., 2019; Dubovičienė & Skorupa, 2014; Niken et al., 2013; Suryasa, 2016), but we focus on headlines in internet advertisements, particularly websites. The headlines were analyzed using linguistic feature theories in four levels: phonological, lexical, syntactic, and semantic levels. The analysis discusses the linguistic features used in the coworking spaces’ home page, the use of the linguistic features in the content, and the effectiveness in attracting readers. Data collected for the study include 59 websites from a coworking space reservation platform, Coworker, and interviews with people involved in the industry. Results of the study show that headlines in coworking space websites prominently use alliteration, noun phrases, and hyperbole. Unlike headlines of printed media, digital media has to comply with search engine optimization (SEO) guidelines so that search engines will index the website properly. HIGHLIGHTS: Linguistic features used in website headlines have several elements in common with headlines in different ad channels, like TVs and printed ads. The main difference between headlines in a digital and printed advertisement is the use of search engine optimization (SEO) strategies in online channels. People’s educational and professional backgrounds can influence how they interpret headlines on websites.